THE MODERNISED PUBLIC SECTOR: IMPLICATIONS FOR NEGATIVE WORKPLACE INTERACTIONS AND BULLYING - Omari, Maryam; Standen, Peter (The journal of contemporary issues in business and government, 2007)
Organisations today function in complex and dynamic environments that exert continual pressure on them to change and compete. Employees are often seen as a key to success in this world, being flexible and adaptable resources; however, the quality of an employee’s work life plays an important role in ensuring they reach their full potential. The Australian Public Service (APS) has undergone significant changes in the last decade. These have impacted all aspects of work, including workplace interactions amongst employees. This paper reports an exploratory study of negative workplace interactions, also called bullying, amongst colleagues in the APS. Of special interest were the internal organisational forces that created and maintained bullying in the APS. Seven internal organisational factors of significance were identified: structure and size; policies and practices; accountability; culture and climate; leadership and role modelling; the nature of work; and generational differences